Fractional order modeling of a nonlinear electromechanical system - Mejia Salazar, Carlos Enrique; Rendón Roldán, Julián Esteban (Enfoque UTE, 2018)
This paper presents a novel modeling technique for a VTOL electromechanical nonlinear dynamical system, based on fractional order derivatives. The proposed method evaluates the possible fractional differential equations of the electromechanical system model by a comparison against actual measurements and in order to estimate the optimal fractional parameters for the differential operators of the model, an extended Kalman filter was implemented. The main advantages of the fractional model over the classical model are the simultaneous representation of the nonlinear slow dynamics of the system due to the mechanical components and the nonlinear fast dynamics of the electrical components.